Household costs of dengue illness: secondary outcomes from a randomised controlled trial of dengue prevention in Guerrero state, Mexico - José Legorreta-Soberanis; Sergio Paredes-Solís; Arcadio Morales-Pérez; Elizabeth Nava-Aguilera; Felipe René Serrano-de los Santos; Diana Lisseth Dimas-Garcia; Robert J Ledogar; Anne Cockcroft; Neil Andersson (BMC, 2017)
Abstract Background Dengue is a serious public health problem with an important economic impact. This study used data from a cluster randomised controlled trial of community mobilisation for dengue prevention to estimate the household costs of treatment of dengue illness. It examined the economic impact of the trial intervention in the three coastal regions of Mexico's Guerrero State. Methods The 2010 baseline survey covered households in a random sample of 90 clusters in the coastal regions; the clusters were randomly allocated to intervention or control and re-surveyed in 2012. The surveys asked about dengue cases in the last 12 months, expenditures on their treatment, and work or school days lost by patients and care givers. We did not assign monetary value to days lost, since a lost day to a person of low earning power is of equal or higher value to that person than to one who earns more. Results The 12,312 households in 2010 reported 1020 dengue cases in the last 12 months (1.9% of the sample population). Most (78%) were ambulatory cases, with a mean cost of USD 51 and 10.8 work/school days, rising to USD 96 and 11.4 work/school days if treated by a private physician. Hospitalised cases cost USD 28-94 in government institutions and USD 392 in private hospitals (excluding additional inpatient charges), as well as 9.6-17.3 work/school days. Dengue cases cost households an estimated 412,825 work/school days throughout the three coastal regions. In the follow up survey, 6.1% (326/5349) of households in intervention clusters and 7.9% (405/5139) in control clusters reported at least one dengue case. The mean of days lost per case was similar in intervention and control clusters, but the number of days lost from dengue and all elements of costs for dengue cases per 1000 population were lower in intervention clusters. If the total population of the three coastal regions had received the intervention, some 149,401 work or school days lost per year could have been prevented. Conclusion The economic effect of dengue on households, including lost work days, is substantial. The Camino Verde trial intervention reduced household costs for treatment of dengue cases. Trial registration The trial was registered as ISRCTN:27,581,154 .